GRAMMATICAL EXPRESSION OF BUGIS POLITENESS - Mahmud, Murni (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
This paper discusses the use of grammar as a strategy to express politeness in Bugis society. This is based on the research I conducted in 2005 in two different Bugis communities: the first was in Awangpone, a rural area and the second was in Parepare. There are three main aspects of Bugis grammar used by Bugis people to encode their politeness. The first one is the pronoun system, in which Bugis speakers use idi’, ta-, or -ki, (the 1st plural inclusive pronoun) to address people politely rather than using iko, mu-, and –nu (the 2nd person pronoun). The second one is the use of participant avoiders such as passive voice di- or terms such as tauwé ‘people’ or anu ‘something or someone’ to avoid mentioning the subject or object directly. Another device is the phonological alternations between final –o and final –i/–é, in which final –o is less polite than final –i/–é such as the pairs iyé’/iyo ‘yes’ or –mi/-mo ‘just’.